(untitled) (Research, Society and Development, 2021)
This paper, which is based on a Master’s thesis, aims at introducing educational experiences developed by the Cirandar Project: investigation groups in school and their contribution to teachers’ continuing Education. Its assumption was that continuing Education requires commitment, availability, listening skills and knowledge sharing. Data were collected in diaries written by a group of teachers who took part in the Cirandar Project developed in Rio Grande, Rio Grande do Sul, Brazil, and analyzed by the Discursive Textual Analysis, the methodology proposed by Moraes and Galiazzi. Results showed that participation in the Cirandar Project stimulated listening to and acknowledging others, besides triggering the development of collective pedagogical practices that contribute to teachers’ identification with their occupations. The study highlighted the importance of sharing teaching practices, welcoming, reflection on school events and encouragement of teachers’ autonomy to (re)signify teaching practices.